UPAYA MENINGKATKAN PARTISIPASI MURID DALAM KEGIATAN DISKUSI KELOMPOK MELALUI LKPD TERSTRUKTUR BERBASIS TUTOR SEBAYA PADA PEMBELAJARAN IPAS KELAS IV - Prasetiyo, Gangga Yoyok; Nugroho, Kusumah; Zahra, Ava Vahdiana; Ayundasari, Fira; Maulina, Indri Nuraini; Zulfa, Hersukma Indri Indana; Fiantika, Feny Rita; Ngayuti, Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of student participation in group discussions, which stood at 30.4%. The purpose of this study was to increase student participation in group discussions through the use of structured worksheets in IPAS instruction. To increase student participation, a classroom action research (CAR) study was conducted over three cycles. This study was conducted from April to May 2026 with a sample of 27 fourth-grade students at SDN Pradah Kalikendal 1 in Surabaya. The instruments used were observation sheets and structured worksheets. Data analysis techniques employed descriptive quantitative methods for quantitative data and descriptive methods for qualitative data. Each cycle included the stages of planning, implementation of actions, observation, and reflection. In Cycle I, three meetings were held, with a student participation rate of 34.2%. These observations indicated that the worksheets were not yet effective in optimally stimulating student participation in discussions. Based on this reflection, improvements were made in Cycle II by implementing structured worksheets designed for three sessions, focusing on collaboration, the use of appropriate learning models, and the addition of activities that stimulate collaborative participation. Through the reflection on Cycle II, the structured worksheets were implemented with group reconfiguration in Cycle III over two sessions. The research results showed a significant increase in student enthusiasm and participation, from 34.2% in Cycle I to 68% in Cycle II, representing an increase of 33.8%. Student participation in Cycle III was 91.6%, an increase of 23.6%. These findings demonstrate that structured worksheets are effective in enhancing student participation in group discussions during IPAS instruction.